2010
DOI: 10.1111/j.1440-1738.2010.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy of the mid‐ to upper‐Cretaceous System in the Aridagawa area, Wakayama, Southwest Japan

Abstract: The litho-and biostratigraphy of the mid-to upper-Cretaceous System around the Yagumaike Pond in the Aridagawa area, Wakayama, Southwest Japan, were investigated. Many Middle to Late Albian megafossils were found in the strata of a block bounded by faults. It was also revealed that the Upper Cretaceous System of other blocks ranges from the Middle Turonian to Santonian. The Albian megafossil assemblage contains few benthic organisms, in contrast with the abundance of nektons found (e.g. cephalopods). Sedimento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The Hinoshima Formation yields Santonian to lower Campanian ammonoid assemblage consisting of Texanites kawasakii , Protexanites fukazawai and Gaudryceras tenuiliratum (Kojo et al, ; Ueda, ). T. kawasakii and P. fukazawai are recognized as important age diagnostic species of the Santonian to lowermost Campanian (Misaki & Maeda, ; Okamoto, Matsunaga, & Okada, ; Toshimitsu, ; Toshimitsu & Hirano, ). The Santonian ammonoid Texanites collignoni was reported from the lower part of the Hinoshima Formation (Ueda, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Hinoshima Formation yields Santonian to lower Campanian ammonoid assemblage consisting of Texanites kawasakii , Protexanites fukazawai and Gaudryceras tenuiliratum (Kojo et al, ; Ueda, ). T. kawasakii and P. fukazawai are recognized as important age diagnostic species of the Santonian to lowermost Campanian (Misaki & Maeda, ; Okamoto, Matsunaga, & Okada, ; Toshimitsu, ; Toshimitsu & Hirano, ). The Santonian ammonoid Texanites collignoni was reported from the lower part of the Hinoshima Formation (Ueda, ).…”
Section: Discussionmentioning
confidence: 99%
“…Shigeta et al (2012) found new index fossils indicating Maastrichtian from the strata which were estimated to be Santonian or Campanian in the Shimizu area (Hirayama & Tanaka, 1956b). Therefore, a geological map ( Figure 3a) was created to confirm the Hirayama & Tanaka (1956a,1956b, Kashiwagi (1999), Kurimoto et al (1998), Maejima (1986), (2009), Misaki & Maeda (2010), Shigeta et al (2012), Tanaka (1985), Yamamoto (1989), and Yao (1984). Fm., Formation with lenticular conglomerates.…”
Section: Maastrichtian Sandstone and Granitic Clastsmentioning
confidence: 96%
“…These strata have yielded a large number of animal and plant fossils, and these and their associated stratigraphy have been studied in detail for a long time (e.g. Hirayama & Tanaka, , ; Matsumoto, ; Misaki, ; Misaki, Kadota, & Maeda, ; Misaki & Maeda, , ; Misaki & Ohara, ; Shigeta, Misaki, & Ohara, ; Tanaka, ). Initiation of sedimentation of the basin is Oxfordian (Kashiwagi & Yao, ).…”
Section: Geological Settingmentioning
confidence: 99%